(untitled) (Bangladesh Journal of Zoology, 2024)
Present study evaluated the toxicity of the leaf extracts of the plant Aegle marmelos(L.) Corrêa against the 4th instar larvae of the mosquito Culex quinquefasciatus Say (Diptera: Culicidae). The experiment was conducted in the ambient environment of the laboratory at the temperature (29 ± 2)ºC and (75-85)% relative humidity. Three solvents were used (viz. ethanol, chloroform and distilled water). A total of 25 actively swimming 4th instar larvae of the mosquito were exposed to various dose concentrations of the plant leaf extracts for 24 hours. Larval mortality was observed after 24 hours of exposure. For ethanol based leaf extracts, the larval mortality of mosquito at five different concentrations, viz. 2.0, 3.0, 4.0, 5.0 and 6.0 mg/ml were 5.33%, 44%, 56%, 73.33% and 97.33%, respectively. Chloroform based leaf extracts were tested with five different concentrations viz. 0.5, 1.0, 1.5, 2.0 and 2.5 mg/ml at which the extracts showed 9.33%, 25.33%, 56%, 94.66% and 100% larval mortality, respectively. For the water based extracts, the dose concentrations were viz. 2.0, 4.0, 6.0, 8.0 and 10.0 mg/ml at which the extracts exerted 30.66%, 54.66%, 60%, 68% and 90.66% larval mortality, respectively. With each dose 2 ml of dimethyl sulfoxide (DMSO) was added to make the extracts soluble in water. The LC50 and LC90 values for ethanol based leaf extracts were 3.530 mg/ml, 5.836 mg/ml and 8.793 mg/ml, respectively. For chloroform based leaf extracts, values were 1.184 mg/ml, 2.127 mg/ml and 3.430 mg/ml, respectively. For distilled water based leaf extracts, values were 3.730 mg/ml, 15.502 mg/ml and 49.521 mg/ml, respectively. The relative potency of three types of leaf extracts of Aegle marmelosagainst the larvae of Culex quinquefasciatus on the basis of , and values are as follows in decreasing order: chloroform based extract ( = 1.184 mg/ml, = 2.127 mg/ml and = 3.430 mg/ml) ˃ ethanol based extract ( = 3.530 mg/ml, = 5.836 mg/ml and = 8.793 mg/ml) ˃ water based extract ( = 3.730 mg/ml, = 15.502 mg/ml and = 49.521 mg/ml). It was found that chloroform extracts showed greater mortality of larvae of Cx. quinquefasciatus than the ethanol extracts and that of the water extracts. From the results it can be concluded that the different solvent based crude extracts of the leaf of A. marmeloswas an excellent potential for controlling Cx. quinquefasciatus mosquito larvae. Bangladesh J. Zool. 52(1): 119-132, 2024